Research on Energy Storage Flywheel Motor Drive Control Technology - Jing, Lili; Dong, Yongsheng (International Journal of Electric Power and Energy Studies, 2024)
Currently there is a way to use for energy storage: batteries for chemical energy storage, super for electric field energy storage, and flywheel batteries for mechanical energy storage. Flywheel energy storage has the advantages of high energy storage density, high efficiency, short charging time, no pollution, wide applicability, no noise, long service life, easy maintenance and continuous operation. Recently the most promising and competitive new energy storage technology - flywheel energy storage technology, relative to other forms of energy storage, by domestic and foreign experts unanimously optimistic. This paper will focus on the composition and operation principle of flywheel energy storage system, the classification of drive control strategy, charging control strategy, discharge control strategy and other aspects.